Lnc-GD2H Promotes Proliferation by Forming a Feedback Loop With c-Myc and Enhances Differentiation Through Interacting With NACA to Upregulate Myog in C2C12 Myoblasts - Chen, Rui; Lei, Si; She, Yanling; Zhou, Shanyao; Shi, Huacai; Li, Cheng; Jiang, Ting (Frontiers in Cell and Developmental Biology, 2021)
In the present study, the roles of a novel long non-coding RNA (lncRNA), lnc-GD2H, in promoting C2C12 myoblast proliferation and differentiation and muscle regeneration were investigated by quantitative polymerase chain reaction, western blotting, Cell Counting Kit-8, 5-ethynyl-2'-deoxyuridine (EdU), immunofluorescence staining, luciferase reporter, mass spectrometry, pulldown, chromatin immunoprecipitation, RNA immunoprecipitation assay, wound healing assays, and cardiotoxin (CTX)-induced muscle injury assays. It was observed that lnc-GD2H promoted myoblast proliferation as evidenced by the enhancement of the proliferation markers c-Myc, CDK2, CDK4, and CDK6, percentage of EdU-positive cells, and rate of cell survival during C2C12 myoblast proliferation. Additional experiments confirmed that c-Myc bound to the lnc-GD2H promoter and regulated its transcription. lnc-GD2H promoted cell differentiation with enhanced MyHC immunostaining as well as increased expression of the myogenic marker genes Myog, Mef2a, and Mef2c during myoblast differentiation. Additional assays indicated that lnc-GD2H interacted with NACA which plays a role of transcriptional regulation in myoblast differentiation, and the enrichment of NACA at the Myog promoter was impaired by lnc-GD2H. Furthermore, inhibition of lnc-GD2H impaired muscle regeneration after CTX-induced injury in mice. lnc-GD2H facilitated the expression of proliferating marker genes and formed a feedback loop with c-Myc during myoblast proliferation. In differentiating myoblasts, lnc-GD2H interacted with NACA to relieve the inhibitory effect of NACA on Myog, facilitating Myog expression to promote differentiation. The results provide evidence for the role of lncRNAs in muscle regeneration and are useful for developing novel therapeutic targets for muscle disorders.